Effect of Salinity on Growth and Survival of Rohu, Labeo rohita (Ham.) under Laboratory and Field Conditions - pillai, Devika; Jose, Susheela; M.V., Mohan; Joseph, Aneykutty (Fishery Technology, 2025)
The limits of salinity affecting survival and growth performance of the Indian Major Carp, Labeo rohita was studied in laboratory and field conditions. A salinity range of 0 tol4 ppt was used at 2 ppt interval in the present study. Rohu could survive in waters upto 8 ppt salinity. Beyond 8 ppt, the fish showed signs of stress and mortality occurred. There was 100% mortality in 14 ppt salinity within 7-8 days. Although maximum growth was obtained at 0 and 2 ppt, growth was not markedly affected upto 6 ppt salinity. Rohu was cultured along with milkfish in brackish water pond, where salinity ranged from 1.9-8.9 ppt during the culture period of 120 days. As salinity increased above 8 ppt, Rohu showed stress signs and therefore, the culture was discontinued. The present study indicates that there is good potential for culturing these species in low saline areas, that otherwise remain unutilized.